Initiation and continuation of breastfeeding among Jordanian first-time mothers: a prospective cohort study - Al dasoqi K; Safadi R; Badran E; Basha AS; Jordan S; Ahmad M (Dove Medical Press, 2018)
Khadeejeh Al dasoqi,1 Reema Safadi,1 Eman Badran,2 Asma Sa’d Basha,3 Sue Jordan,4 Muayyad Ahmad5 1Department of Maternal and Child Health Nursing, School of Nursing, University of Jordan, Amman, Jordan; 2Department of pediatrics, School of Medicine, University of Jordan, Amman, Jordan; 3Department of Obstetrics and Gynecology, School of Medicine, University of Jordan, Amman, Jordan; 4Department of Nursing, Swansea University, Swansea, UK; 5Clinical Nursing Department, School of Nursing, University of Jordan, Amman, Jordan Objective: This study aimed to examine the rates of initiation and continuation of breastfeeding (BF) and their relationship with mothers’ sociodemographic, obstetric, neonatal, and medical interventions.Methods: Data were collected from 199 first-time Jordanian mothers using medical records, face-to-face interviews within 24 hours of birth, and two telephone interviews at 6 weeks and 6 months after birth.Results: The rate of BF initiation within the first 4 hours after birth was only 13%. The rate of exclusive BF at 6 weeks was 25.5%, and this rate dropped to 2.1% at 6 months. Mothers who initiated BF before discharge were older, were employed, had normal vaginal birth, and had undergone antenatal or after-birth BF education. Infants’ birth weight or gender was not interrelated with BF initiation. There was no relationship between initiation and continuation of BF and use of medications for labor pain or for induction/augmentation. The only significant relationship was found between the dose of ergometrine and BF failure and painful BF at 6 weeks.Conclusion: There is a need for increasing health care providers and public awareness about the role of intrapartum medications and procedures on the initiation and continuation of BF at 6 weeks and 6 months after birth. Keywords: exclusive breastfeeding, ergometrine, obstetric procedures, intrapartum medication, Jordan